2023
DOI: 10.1021/acsomega.3c01262
|View full text |Cite
|
Sign up to set email alerts
|

Testing of Sr-Doped ZnO/CNT Photocatalysts for Hydrogen Evolution from Water Splitting under Atmospheric Dielectric Barrier Plasma Exposure

Abstract: Nonthermal plasma is a well-recognized environmentally advantageous method for producing green fuels. This work used different photocatalysts, including PZO, S x ZO, and S x ZC x for hydrogen production using an atmospheric argon coaxial dielectric barrier discharge (DBD)-based light source. The photocatalysts were produced using a sol–gel route. The DBD discharge column was filled with water, methanol, and the catalyst to run the reaction under argon plasma. The DBD reactor was operated with a 10 kV AC sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Several reports from previous studies also revealed that nanotubes photocatalysts perform much better than bulk and 2D photocatalyst materials [12]. Photocatalytic hydrogen evolution tests were conducted on Sr-doped ZnO/CNT photocatalyst by Irfan et al [13]. They reported that S 25 ZC 2 demonstrated a high rate of hydrogen evolution of the order of 2760 μmolh −1 g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Several reports from previous studies also revealed that nanotubes photocatalysts perform much better than bulk and 2D photocatalyst materials [12]. Photocatalytic hydrogen evolution tests were conducted on Sr-doped ZnO/CNT photocatalyst by Irfan et al [13]. They reported that S 25 ZC 2 demonstrated a high rate of hydrogen evolution of the order of 2760 μmolh −1 g −1 .…”
Section: Introductionmentioning
confidence: 99%